Investigating health literacy and sociodemographic factors in college students - Sudhakar, Shyam Kumar; Doshi, Divij Pranay; Nair, Gayathri; Rao, Tejas (Scientific reports, 2025)
Health literacy is a vital constituent of public health in the country. Frequently overlooked in research studies, health literacy is an important multidimensional construct essential for building a robust healthcare system across the country. Health literacy is vital for college students as it provides the necessary skills and information to make health-related decisions and better manage their health. This study aims to understand various aspects of health literacy and its correlation with sociodemographic determinants in a population of college students. The study employs a cross-sectional design with a sample size of 200 students. The health literacy of the subjects was assessed using the health literacy questionnaire (HLQ). In addition, sociodemographic information was also collected from the participants. Univariate (ANOVA) and multivariate (MANOVA) statistical methods were employed to understand how the subjects’ health literacy was affected by various sociodemographic factors. Among the nine individual scales of the HLQ, the subjects in our study possess increased social support for health and the ability to diligently participate in discussions with health professionals to learn about their health. Importantly, health literacy is affected by subscription to health insurance ( p = 0.0024), physical activity status ( p = 0), and family income of the participants ( p = 0.0001). Health insurance affected eight scales of the HLQ, physical activity affected five scales, and family income affected seven scales, with small to moderate effect sizes observed for most cases (ANOVA). We did not find any significant effects of consumption of prescription medication, year and discipline of study, the presence of chronic illness, and food preference of the subjects on health literacy, while a weak effect of gender was noticed. The study points to the existence of noticeable differences in college students’ health literacy across various sociodemographic groups. By identifying disparities in various HLQ scales among different sociodemographic groups, this study paves the way for designing focused training activities for student groups with lower scores. Such curricular interventions would enable students to manage their health effectively, leading to equitable health results among the student population.